Efeito residual de fosfatos naturais parcialmente acidificados com H3PO4, HCl e H2SO4 em sorgo granífero (Sorghum bicolor (L) Moench):: produção de matéria seca total - Bueno , Newton; Braga, José Mário; L Thiébaut, José Tarcísio; Franco , Marcelo (Revista Ceres, 2025)
Experiments were carried out to study the behavior of phosphoric, hydrochloric and sulphuric acids in the partial acidification of natural phosphates and to verify the efficiency of this treatment as a source of residual phosphorus in the production of dry matter in plants.